Silk nanocrystal (SNC) reinforced poly (lactic acid) based microcellular foam: Impact on porous structure, crystallinity, thermomechanical and surface property. (June 2021) - Borkotoky, Shasanka Sekhar; Ghosh, Tabli; Patwa, Rahul; Katiyar, Vimal
Graphical abstract: Highlights: The study investigates the development of PLA/SNC based nanocomposite microcellular foams. Using SNC as nanofiller improves the crystallinity of PLA based biocomposite foams. SNC as biofiller offers improved thermo-mechanical attributes to developed foams. PLA/SNC based foams provide better thermal stability than neat PLA foams. Surface properties of PLA/SNC foams are modified using SNC as reinforcements. Abstract: The current research addresses the fabrication of poly (lactic acid) (PLA)/silk nanocrystal (SNC) biocomposite based highly porous, lightweight, and interconnected microcellular foam using a simple and cost-effective approach. The nanofiller SNC was fabricated from muga cocoons following degumming and acid hydrolysis methods. In the developed biocomposite foam, SNC as a nanofiller helps to improve the crystallinity of PLA, where, SNC acts as a nucleating agent and further helps to generate smaller pores in the matrix improving the foam properties. Additionally, the cell size of SNC (at 3% loading) incorporated PLA microcellular foams decreases up to ∼60 % compared to neat PLA (nPLA) foam. The density of the biocomposite foam is observed to be reduced effectively by ∼85 % in comparison to nPLA. In case of thermal property, PLA/SNC based foams have effective thermal stability up to ∼250 °C, whereas nPLA foams are thermally stable upto ∼200 °C. Interestingly, SNC as biofiller also offers improved thermo-mechanical properties to foams, which are desirable for advanced engineering applications. Further, the improved hydrophobicity of PLA/SNC based foams may be obtained due to the combined effect of surface texture, nanofillers and porogen materials. Based on this study, the fabricated PLA/SNC based foams are considered as a potential candidate in biomedical, packaging, and several versatile areas for the mentioned noteworthy attributes.